The mediating role of emotion on the relationship between festival quality and loyalty / Hassnah Wee - Wee, Hassnah (2016)
Examining the role of event visitors' emotion towards loyalty has recently increased in the research studies which diminishing the impact of event visitors satisfaction towards loyalty. The outcome of emotion as mediator has resulted a mix findings from past studies. Emotion is said to be a predictor to loyalty in various environment and study setting. Nevertheless, the role of emotion as mediator within the Stimulus- Organism-Response paradigm in event tourism setting is very limited. Therefore, this study intends to validate and expand research areas in festival setting by integrating theories, models, and constructs within the behavioural context of event tourism to explain the complex process of environmental stimuli and visitors' emotions and loyalty. This study specifically focuses on examining the effect of festival quality (service performance quality and perceived service quality) on visitors' loyalty directly or indirectly when emotion is the mediating factor. The Stimulus-Organism-Response (SOR) paradigm was the chosen underpinning theory with modified Mehrabian-Russell model was used as the conceptual framework for this study. A structural equation modelling software (Analysis of Moment Structures or AMOS) was applied to examine the direct and mediating effects hypotheses. The sampling design was systematic random sampling with 360 targeted respondents from the Rainforest World Music Festival visitors. The data analyses were conducted based on the one-step pooled confirmatory factor analysis (CFA) in testing seven hypotheses, which all were supported. The findings from this study point to support the modified Mehrabian-Russell emotional model of environmental psychology paradigm within event tourism setting. All hypotheses were resulted with significant relationship among the four latent constructs (Service Performance Quality, Perceived Service Quality, Emotion and Loyalty). However, results of mediation analysis indicated that both paths between Festival Quality and Loyalty provides partial mediation when Emotion enters the model. The conceptual framework used in this study offers a good starting point for examining emotional consumption experience dimension in event tourism future research. The study outcomes provide implications for theoretical, methodological, industry, and practical and managerial perspectives.